Resisting Racism Through Feminist and Pragmatics Theory: An Exploration of Minority Nurses' Experience in Makassar - Nur Fitriani; Mauliyanda Sam Dg Ngai; Sri Maulidya Bakri; Nur Aqila Athifa; Arini Junaeny (Interference: Journal of Language, Literature, and Linguistics, 2025)
Abstract. This study explores the experiences of minority nurses in Makassar City who face racism in the workplace, using feminism and pragmatics theories. The high incidence of racism negatively impacts the psychological and professional well-being of minority nurses. This study aimed to understand minority nurses' responses and strategies to racism and identify expected support from hospital management. A qualitative method with purposive sampling was used to select informants, with data collected through in-depth interviews and participant observation. The results show that minority nurses face various forms of racism, such as prejudice, stereotyping, discrimination, and segregation. Based on the analysis from a feminist perspective, most of the key informants said there was no significant difference in the division of tasks between male and female nurses. Other informants stated that there were prominent differences in the division of tasks between nurses based on gender. Positively, results showed that informants were professional and calm in the face of racism, using strategies such as sharing stories with coworkers, pursuing hobbies, and exercising to reduce pressure. Informants expected strict sanctions for perpetrators of racism and anti-racism training for the new workforce. In conclusion, institutional support and clear policies are needed to protect the rights of minority nurses and address racism in the workplace. Keywords: Nurse, Minority, Racism, Feminism,   Pragmatics